Komunikasi Budaya Berbalas Pantun Telangkai Adat Pernikahan Melayu Deli - Al Fathir, Ihsan; Sazali, Hasan; Rasyid, Abdul (Comit: Communication, Information and Technology Journal, 2025)
Cultural communication through the exchange of traditional Pantun verses by Telangkai during Malay Deli weddings is an example of communication within the Malay Deli community during marriage ceremonies. Telangkai themselves are the elders (masters of ceremonies) of customs in the marriage process of the Malay Deli people. This research was conducted using a qualitative research approach with descriptive qualitative methods. According to Bogdan and Taylor, qualitative research methods include research procedures that can produce data in the form of spoken words, sentences, and photos but not in numerical form from observed people and behaviors. Based on research conducted on Telangkai members affiliated with the Association of Telangkai Custodians of Malay Customs (HITPAM), as well as in the Malay Cultural Cluster organization, and through interactions with the community involved in the Malay Deli traditional wedding process, it can be concluded that the communication performed by Telangkai is direct verbal communication.